Genome editing and the next generation of antiviral therapy - Stone, Daniel (Hum Genet, 2016)
Engineered endonucleases such as homing endonucleases (HEs), zinc finger nucleases (ZFNs), Tal-effector nucleases (TALENS) and the RNA-guided engineered nucleases (RGENs or CRISPR/Cas9) can target specific DNA sequences for cleavage, and are proving to be valuable tools for gene editing. Recently engineered endonucleases have shown great promise as therapeutics for the treatment of genetic disease and infectious pathogens. In this review, we discuss recent efforts to use the HE, ZFN, TALEN and CRISPR/Cas9 gene-editing platforms as antiviral therapeutics. We also discuss the obstacles facing gene-editing antiviral therapeutics as they are tested in animal models of disease and transition towards human application.